Gerbang Sebagai Pembentuk Identitas Kawasan Wisata Situs Gunung Padang - Devina Marshanda; Lia Rosmala Schiffer; Rehulina Apriyanti (Program Studi Arsitektur Fakultas Teknik Universitas Mataram, 2023)
The gate of the Gunung Padang Site Tourism Area located in Karyamukti Village, Gunung Padang Hamlet, Campaka District, Cianjur Regency, West Java, is a gate as a shaper of the identity or image of the Gunung Padang Site. The padang mountain site attracts tourists and scientists because of its rock site that was built in 8000 BC. However, this tourist area will be developed into a tourist area with various tourist destinations to attract more tourists. So that the redesign of the existing gate is needed that can provide an area identity that is lifted from the cultural values in Karyamukti Tourism Village. Identitas the shape of the new gate design is taken from the shape of kujang, rice on the district logo and represents the tea plantations in Karyamukti Tourism Village. From the redesign of the existing gate, it is hoped that the redesign of the gate will provide added value based on the potential that will be developed in Karyamukti Tourism Village. For this study, the data collection method used methods by means of field surveys, direct observations at the study site, interviews with speakers, taking video photo documentation from each angle, gate measurements to analyze tourist gate standards, gate sketches and all data collected in one storage for this study.